Composite stainless steel pipe coated with corrosion-resistant layer on surface and preparation method of composite stainless steel pipe

By coating the corrosion-resistant layer made of polyacrylate modified methyl silicone resin and other materials on the stainless steel pipe, the corrosion problem of stainless steel pipes in high humidity and heat environments in the ocean is solved, the corrosion resistance and wear resistance are improved, and the corrosion resistance and wear resistance are extended. Service life.

CN119196449APending Publication Date: 2024-12-27JIANGSU XINYANGGUANGGUANYE SCI & TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411109935.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-14
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In the environment of high humidity and heat in the ocean, high salt spray and high chloride ion concentration, stainless steel pipes are prone to pitting corrosion, resulting in reduced performance and shortened service life. In the existing anti-corrosion process, the paint layer has poor wear resistance and is prone to fall off.

Method used

Using composite stainless steel pipes coated with corrosion-resistant layer, the coating liquid consists of polyacrylate modified methyl silicone resin, nano SiC, sodium dodecyl sulfonate and silane coupling agent to form corrosion-resistant through specific preparation methods. The corrosion resistance and bond strength of stainless steel pipes are improved.

Benefits of technology

It significantly improves the corrosion resistance and wear resistance of stainless steel pipes, avoids the corrosion-resistant layer falling off, and extends the service life of stainless steel pipes.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of pipe manufacturing, in particular to a composite stainless steel pipe coated with a corrosion-resistant layer on the surface and a preparation method thereof.The composite stainless steel pipe is composed of a stainless steel pipe body and the corrosion-resistant layer coated on the surface of the stainless steel pipe body, and the stainless steel pipe body comprises, by mass, 14%-18% of Cr, 6%-9% of Ni, 0.6%-1.2% of Mn, 0.02%-0.08% of C, 0.3%-0.6% of Si, 1.0%-1.6% of Cu and the balance Fe; the corrosion-resistant layer is formed by curing a coating liquid, and the coating liquid comprises the following components in percentage by mass: 25-30% of polyacrylate modified methyl silicone resin, 6-12% of nano SiC, 4-8% of sodium dodecyl sulfate, 2-4% of a silane coupling agent and the balance of ethyl acetate; the surface of the stainless steel pipe is coated with the corrosion-resistant layer, the corrosion resistance of the stainless steel pipe is improved, the stainless steel pipe is prevented from being corroded, the bonding strength of the corrosion-resistant layer and the stainless steel pipe is high, the wear resistance is excellent, and the corrosion-resistant layer can be effectively prevented from falling off from the stainless steel pipe.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of pipe manufacturing, and in particular to a composite stainless steel pipe with a corrosion-resistant layer coated on the surface and a preparation method thereof. Background Art

[0002] Stainless steel pipe is a hollow long round steel. It has been widely used in all walks of life. The alloy of stainless steel pipe itself contains nickel, chromium and other components. Under normal conditions, stainless steel pipe will not rust, so stainless steel pipe has good corrosion resistance.

[0003] However, in the high humidity, high salt spray, and high chloride ion concentration environment of the ocean, pitting corrosion will occur on the stainless steel pipe, resulting in a decrease in the performance of the stainless steel pipe and a shortened service life. The current anti-corrosion process for stainless steel pipes is mainly to paint the surface of the stainless steel pipe, but the paint layer has poor wear resistance and is easily peeled off due to wear, exposing the stainless steel pipe to a corrosive environment. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a composite stainless steel pipe with a corrosion-resistant layer coated on its surface and a preparation method thereof.

[0005] The technical solution of the present invention is: a composite stainless steel pipe with a corrosion-resistant layer coated on the surface, which is composed of a stainless steel pipe and a corrosion-resistant layer coated on the surface of the stainless steel pipe, wherein the components of the stainless steel pipe include, by mass percentage, 14-18% Cr, 6-9% Ni, 0.6-1.2% Mn, 0.02-0.08% C, 0.3-0.6% Si, 1.0-1.6% Cu, and the rest is Fe;

[0006] The corrosion-resistant layer is formed by curing the coating liquid, and the components of the coating liquid include, by mass percentage: 25-30% of polyacrylate-modified methyl silicone resin, 6-12% of nano-SiC, 4-8% of sodium dodecyl sulfonate, 2-4% of silane coupling agent, and the balance is ethyl acetate.

[0007] Description: The surface of the above-mentioned stainless steel pipe is coated with a corrosion-resistant layer, which improves the corrosion resistance of the stainless steel pipe and prevents the stainless steel pipe from being corroded. The corrosion-resistant layer has high bonding strength with the stainless steel pipe and excellent wear resistance, which can effectively prevent the corrosion-resistant layer from falling off the stainless steel pipe.

[0008] Furthermore, the silane coupling agent is a mixture of any one or more of vinyl trichlorosilane, vinyl trimethoxysilane, vinyl triethoxysilane, and 3-aminopropyl triethoxysilane in any ratio.

[0009] Description: The above silane coupling agent can improve the dispersibility of nano-SiC and the binding property between nano-SiC and polyacrylate-modified methyl silicone resin, so that nano-SiC can be evenly dispersed in the coating, improve the wear resistance of the coating, and prevent the nano-SiC from falling off.

[0010] Furthermore, the preparation method of the polyacrylate-modified methyl silicone resin comprises the following steps:

[0011] S1. Add methyltrichlorosilane and dimethyldichlorosilane into xylene and stir for 3-5 minutes to obtain a mixed solution; wherein the mass ratio of methyltrichlorosilane, dimethyldichlorosilane and xylene is 5-7:1-2:20-25;

[0012] S2, using sodium hydroxide aqueous solution to adjust the pH value of the mixed solution to 10-11, after reacting for 1-1.5 hours, adding methyl acrylate to obtain a prepolymer, during the reaction, adding sodium hydroxide aqueous solution to the mixed solution once every 20-30 minutes to adjust the pH value of the mixed solution to 9-10; the amount of methyl acrylate added accounts for 15-20% of the mass of the mixed solution;

[0013] S3, heating the prepolymer to 40-50° C., then adding azobisisobutylnitrile to the prepolymer, continuing to heat the prepolymer to 70-80° C. and keeping the temperature for 10-14 hours under high-speed stirring, and obtaining a polymer after cooling; the amount of azobisisobutylnitrile added accounts for 4-6% of the mass of the prepolymer;

[0014] S4, distilling the polymer to remove xylene to obtain a solid polymer, and washing and drying the solid polymer to obtain a polyacrylate-modified methyl silicone resin.

[0015] Description: The above method modifies the methyl silicone resin by polyacrylate, which has good adhesion, improves the bonding between the methyl silicone resin and the stainless steel pipe, and improves the thermal stability of the methyl silicone resin.

[0016] Furthermore, in step S2, the mass concentration of the sodium hydroxide aqueous solution initially added is 25-30%, and the mass concentration of the sodium hydroxide aqueous solution subsequently added is reduced by 2-4% compared with the previous addition.

[0017] Note: Gradually reducing the concentration of sodium hydroxide aqueous solution can ensure the reaction pH value and control the hydrolysis rate of methyltrichlorosilane.

[0018] Furthermore, in step S3, the stirring speed under the high-speed stirring state is 600-800 r / min.

[0019] Note: Limiting the stirring speed can improve the fluidity of the prepolymer and avoid agglomeration and adhesion of the prepolymer.

[0020] Furthermore, in step S3, the cooling is performed by using ice water at 0 to 5°C to cool the prepolymer.

[0021] Note: Using ice water can ensure that the prepolymer is cooled quickly, so that the polyacrylate-modified methyl silicone resin can be precipitated quickly.

[0022] Furthermore, the coating liquid is prepared by adding nano-SiC to ethyl acetate, ultrasonically dispersing for 10 to 15 minutes, gradually adding a silane coupling agent during the ultrasonic dispersion process, and then adding polyacrylate-modified methyl silicone resin and sodium dodecyl sulfate to ethyl acetate, stirring until completely dissolved, to obtain a coating liquid.

[0023] Note: The coating liquid nano-SiC prepared by the above method can be evenly dispersed in the coating liquid, making the cured coating uniform and dense.

[0024] On the other hand, the present invention provides a method for preparing a composite stainless steel pipe with a surface coated with a corrosion-resistant layer, which is used to prepare the composite stainless steel pipe with a surface coated with a corrosion-resistant layer, comprising the following steps:

[0025] Step 1: grinding, pickling and drying the surface of the stainless steel tube to obtain a pretreated stainless steel tube;

[0026] Step 2: Spray the coating liquid onto the pretreated stainless steel pipe surface. The spraying amount of the coating liquid is 20-30 ml / cm 2 After the coating liquid completely covers the surface of the stainless steel pipe, the stainless steel pipe is placed at 120-140°C and baked for 2-3 hours. After baking, a composite stainless steel pipe with a surface coated with a corrosion-resistant layer is obtained.

[0027] Description: The above preparation method forms a corrosion-resistant layer by solidifying the coating liquid on the surface of the stainless steel pipe. The corrosion-resistant layer has high bonding strength with the stainless steel pipe, and the corrosion-resistant layer has uniform thickness and good consistency, which can effectively improve the corrosion resistance of the stainless steel pipe.

[0028] Furthermore, the pickling method is: immersing the stainless steel pipe in a nitric acid solution with a mass concentration of 10-20% for 15-20 minutes, and after immersion, rinsing the stainless steel pipe with deionized water.

[0029] Note: Pickling can remove oil stains on the surface of stainless steel pipes and ensure that the corrosion-resistant layer can adhere well to the surface of stainless steel pipes.

[0030] The beneficial effects of the present invention are:

[0031] (1) The surface of the stainless steel pipe of the present invention is coated with a corrosion-resistant layer, which improves the corrosion resistance of the stainless steel pipe and prevents the stainless steel pipe from being corroded. The corrosion-resistant layer has high bonding strength with the stainless steel pipe and excellent wear resistance, which can effectively prevent the corrosion-resistant layer from falling off the stainless steel pipe.

[0032] (2) The present invention modifies the methyl silicone resin by using polyacrylate, which has good adhesion, improves the bonding between the methyl silicone resin and the stainless steel pipe, and improves the thermal stability of the methyl silicone resin.

[0033] (3) The preparation method of the present invention forms a corrosion-resistant layer by solidifying the coating liquid on the surface of the stainless steel pipe. The corrosion-resistant layer has a high bonding strength with the stainless steel pipe, and the corrosion-resistant layer has a uniform thickness and good consistency, which can effectively improve the corrosion resistance of the stainless steel pipe. DETAILED DESCRIPTION

[0034] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.

[0035] Embodiment 1: A composite stainless steel pipe with a corrosion-resistant layer coated on the surface, characterized in that it consists of a stainless steel pipe and a corrosion-resistant layer coated on the surface of the stainless steel pipe, wherein the components of the stainless steel pipe include, by mass percentage: Cr 16%, Ni 8%, Mn 0.9%, C 0.06%, Si 0.5%, Cu 1.3%, and the rest is Fe;

[0036] The corrosion-resistant layer is formed by curing the coating liquid, and the components of the coating liquid include, by mass percentage: 28% of polyacrylate-modified methyl silicone resin, 9% of nano-SiC, 6% of sodium dodecyl sulfonate, 3% of silane coupling agent, and the balance is ethyl acetate; the silane coupling agent is vinyl trichlorosilane;

[0037] The preparation method of polyacrylate modified methyl silicone resin comprises the following steps:

[0038] S1. Add methyltrichlorosilane and dimethyldichlorosilane into xylene and stir for 4 minutes to obtain a mixed solution; wherein the mass ratio of methyltrichlorosilane, dimethyldichlorosilane and xylene is 6:1.5:22;

[0039] S2. The pH value of the mixed solution was adjusted to 10.5 using a sodium hydroxide aqueous solution. After reacting for 1.25 hours, methyl acrylate was added to obtain a prepolymer. During the reaction, a sodium hydroxide aqueous solution was added dropwise to the mixed solution every 25 minutes to adjust the pH value of the mixed solution to 9.5. The mass concentration of the sodium hydroxide aqueous solution added initially was 28%, and the mass concentration of the sodium hydroxide aqueous solution added each time was reduced by 3% compared with the previous time. The amount of methyl acrylate added accounted for 18% of the mass of the mixed solution.

[0040] S3, heating the prepolymer to 45°C, then adding azobisisobutylnitrile to the prepolymer, continuing to heat the prepolymer to 75°C under high-speed stirring at 700 r / min and keeping the temperature for 12 hours, and cooling the prepolymer with 2°C ice water to obtain a polymer; the amount of azobisisobutylnitrile added accounts for 5% of the mass of the prepolymer;

[0041] S4, distilling the polymer to remove xylene to obtain a solid polymer, and washing and drying the solid polymer to obtain a polyacrylate-modified methyl silicone resin;

[0042] The preparation method of the coating liquid is as follows: adding nano-SiC to ethyl acetate, ultrasonically dispersing for 12 minutes, gradually adding a silane coupling agent during the ultrasonic dispersion process, then adding polyacrylate-modified methyl silicone resin and sodium dodecyl sulfate to ethyl acetate, stirring until completely dissolved, and obtaining a coating liquid;

[0043] The method for preparing the composite stainless steel pipe with the corrosion-resistant layer coated on the surface comprises the following steps:

[0044] Step 1: grinding, pickling and drying the surface of the stainless steel tube to obtain a pretreated stainless steel tube; the pickling method is: immersing the stainless steel tube in a nitric acid solution with a mass concentration of 15% for 18 minutes, and after the immersion is completed, the stainless steel tube is rinsed with deionized water;

[0045] Step 2: Spray the coating liquid onto the pretreated stainless steel pipe surface at a spray volume of 25 ml / cm 2 After the coating liquid completely covers the surface of the stainless steel pipe, the stainless steel pipe is placed at 130°C and baked for 2.5 hours. After baking, a composite stainless steel pipe with a surface coated with a corrosion-resistant layer is obtained.

[0046] Example 2: This example is basically the same as Example 1, except that the components of the stainless steel pipe include, by mass percentage, Cr 14%, Ni 6%, Mn 0.6%, C 0.02%, Si 0.3%, Cu 1.0%, and the rest is Fe.

[0047] Example 3: This example is basically the same as Example 1, except that the components of the stainless steel pipe include, by mass percentage, Cr 18%, Ni 9%, Mn 1.2%, C 0.08%, Si 0.6%, Cu 1.6%, and the rest is Fe.

[0048] Example 4: This example is basically the same as Example 1, except that the coating liquid comprises, by mass percentage, 25% polyacrylate-modified methyl silicone resin, 6% nano-SiC, 4% sodium dodecyl sulfonate, 2% silane coupling agent, and the balance is ethyl acetate.

[0049] Example 5: This example is basically the same as Example 1, except that the coating liquid comprises, by mass percentage, 30% polyacrylate-modified methyl silicone resin, 12% nano-SiC, 8% sodium dodecyl sulfonate, 4% silane coupling agent, and the balance is ethyl acetate.

[0050] Example 6: This example is basically the same as Example 1, except that the mass ratio of methyltrichlorosilane, dimethyldichlorosilane and xylene is 5:1:20.

[0051] Example 7: This example is basically the same as Example 1, except that the mass ratio of methyltrichlorosilane, dimethyldichlorosilane and xylene is 7:2:25.

[0052] Example 8: This example is basically the same as Example 1, except that the pH value of the mixed solution is adjusted to 10 using sodium hydroxide aqueous solution, and during the reaction process, sodium hydroxide aqueous solution is added dropwise to the mixed solution every 25 minutes to adjust the pH value of the mixed solution to 9.

[0053] Example 9: This example is basically the same as Example 1, except that the pH value of the mixed solution is adjusted to 11 using sodium hydroxide aqueous solution, and during the reaction process, sodium hydroxide aqueous solution is added dropwise to the mixed solution every 25 minutes to adjust the pH value of the mixed solution to 10.

[0054] Example 10: This example is substantially the same as Example 1, except that the mass concentration of the aqueous sodium hydroxide solution initially added is 25%, and the mass concentration of the aqueous sodium hydroxide solution subsequently added is reduced by 2% compared to the previous addition.

[0055] Example 11: This example is basically the same as Example 1, except that the mass concentration of the sodium hydroxide aqueous solution added initially is 30%, and the mass concentration of the sodium hydroxide aqueous solution added subsequently is reduced by 4% compared with the previous time.

[0056] Example 12: This example is basically the same as Example 1, except that the amount of azobisisobutylnitrile added is 4% of the mass of the prepolymer.

[0057] Example 13: This example is basically the same as Example 1, except that the amount of azobisisobutylnitrile added is 6% of the mass of the prepolymer.

[0058] Example 14: This example is basically the same as Example 1, except that the spraying amount of the coating liquid is 20 ml / cm 2 .

[0059] Example 15: This example is basically the same as Example 1, except that the spraying amount of the coating liquid is 30 ml / cm 2 .

[0060] Example 16: This example is basically the same as Example 1, except that the stainless steel tube is baked at 120°C for 2 hours.

[0061] Example 17: This example is basically the same as Example 1, except that the stainless steel tube is baked at 140°C for 3 hours.

[0062] Comparative Example 1: Taking Example 1 as a reference, the surface of the stainless steel pipe is not coated with a corrosion-resistant layer.

[0063] Comparative Example 2: Using Example 1 as a reference, a commercially available anti-corrosion paint was used to replace the corrosion-resistant layer.

[0064] Comparative Example 3: Using Example 1 as a reference, unmodified methyl silicone resin was used to replace the polyacrylate-modified methyl silicone resin.

[0065] Comparative Example 4: Using Example 1 as a reference, the sodium hydroxide aqueous solution was added to the mixed solution all at once.

[0066] Comparative Example 5: With reference to Example 1, the mass concentration of the sodium hydroxide aqueous solution added each time was constant at 28%.

[0067] Experimental example: In order to explore the influence of the parameters of each embodiment on the performance of the stainless steel pipe, the stainless steel pipes of each embodiment and the comparative example were sampled, and the surface coated with the corrosion-resistant layer was selected as the test surface of the sample, and then the remaining surface of the sample was sealed with epoxy resin, and the corrosion resistance and wear resistance of the test surface of each sample were tested; during the corrosion resistance test, the sample was immersed in a NaCl solution with a mass concentration of 3.5% for 30 days, and the mass loss rate before and after immersion was calculated; the load of the wear resistance test was 10N, the test time was 30 minutes, and the wear amount before and after wear was calculated; the specific exploration is as follows:

[0068] 1. Explore the influence of the components of stainless steel pipes on the performance of stainless steel pipes

[0069] Using Examples 1, 2, and 3 as experimental comparisons, the performance of the stainless steel pipes under different components is shown in Table 1 below:

[0070] Table 1 Performance of stainless steel pipes under different components

[0071] Group Mass loss rate before and after immersion / % Wear amount / mg Example 1 0.382 6.5 Example 2 0.374 6.9 Example 3 0.379 6.8

[0072] It can be seen from the data in Table 1 that the components of the stainless steel pipe have little effect on the corrosion resistance. This may be because the corrosion-resistant layer effectively protects the stainless steel substrate, and the stainless steel substrate is not corroded. The sample in Example 1 has the least wear. This may be because the bonding strength between the stainless steel pipe component and the corrosion-resistant layer in Example 1 is the highest, and the corrosion-resistant layer has the least shedding. Therefore, the stainless steel pipe component selected in Example 1 is optimal.

[0073] 2. Investigate the influence of coating liquid composition on the performance of stainless steel pipe

[0074] Using Examples 1, 4, 5 and Comparative Examples 1, 2, 3 as experimental comparisons, the performance of the stainless steel pipe under different coating liquid compositions is shown in Table 2 below:

[0075] Table 2 Performance of stainless steel pipes under different coating liquid compositions

[0076] Group Mass loss rate before and after immersion / % Wear amount / mg Example 1 0.382 6.5 Example 4 0.405 7.1 Example 5 0.398 7.0 Comparative Example 1 0.747 4.9 Comparative Example 2 0.562 9.6 Comparative Example 3 0.549 8.3

[0077] It can be seen from the data in Table 2 that compared with Examples 1, 4, and 5, the mass loss rate of the sample in Example 1 before and after immersion is the smallest, and the wear amount is the least, indicating that the corrosion resistance and wear resistance of the stainless steel pipe in Example 1 are both the best, so the coating liquid composition selected in Example 1 is the best;

[0078] Compared with comparative example 1, in Example 1, the wear amount is reduced after the corrosion-resistant layer is not coated, indicating that the wear resistance of the corrosion-resistant layer is worse than that of the stainless steel substrate. However, the stainless steel pipe will not be exposed to the friction environment for a long time, and the wear resistance of the corrosion-resistant layer can meet the normal use. Moreover, after the corrosion-resistant layer is not coated, the mass loss rate before and after immersion is significantly increased, indicating that the corrosion resistance of the stainless steel pipe is significantly reduced. Therefore, the corrosion-resistant coating can effectively improve the corrosion resistance of the stainless steel pipe.

[0079] Compared with Comparative Example 2, after the corrosion-resistant layer was replaced by commercially available anti-corrosion paint in Example 1, the corrosion resistance of the stainless steel pipe decreased, and the wear amount increased, indicating that the anti-corrosion paint fell off a lot; compared with Comparative Example 3, after the unmodified methyl silicone resin was replaced by polyacrylate-modified methyl silicone resin in Example 1, the corrosion resistance and wear resistance of the stainless steel pipe both decreased, indicating that the methyl silicone resin can effectively improve the corrosion resistance and wear resistance of the corrosion-resistant layer after modification.

[0080] 3. Explore the influence of mixed solution ratio and mixed solution pH value on the performance of stainless steel pipe

[0081] Using Examples 1, 6, 7, 8, and 9 as experimental comparisons, the performance of the stainless steel pipe at different proportions of the mixed solution and different pH values ​​of the mixed solution is shown in Table 3 below:

[0082] Table 3 Performance of stainless steel tubes at different proportions of mixed solutions and different pH values ​​of mixed solutions

[0083] Group Mass loss rate before and after immersion / % Wear amount / mg Example 1 0.382 6.5 Example 6 0.434 7.3 Example 7 0.441 7.4 Comparative Example 8 0.408 7.0 Comparative Example 9 0.411 7.2

[0084] It can be seen from the data in Table 3 that compared with Examples 1, 6, 7, 8, and 9, the proportion of the mixed solution and the pH value of the mixed solution will affect the performance of the stainless steel pipe. Among them, the mass loss rate of the sample in Example 1 before and after immersion is the smallest, and the wear amount is the least, indicating that the corrosion resistance and wear resistance of the stainless steel pipe in Example 1 are the best. Therefore, the proportion of the mixed solution and the pH value of the mixed solution selected in Example 1 are both optimal.

[0085] 4. Investigate the effects of sodium hydroxide aqueous solution concentration and azobisisobutylnitrile addition on the performance of stainless steel pipes

[0086] Using Examples 1, 10, 11, 12, 13 and Comparative Examples 4 and 5 as experimental comparisons, the effects of different concentrations of sodium hydroxide aqueous solution and different addition amounts of azobisisobutylnitrile on the performance of the stainless steel tube are shown in Table 4 below:

[0087] Table 4 Performance of stainless steel pipes at different concentrations of sodium hydroxide aqueous solution and different addition amounts of diisobutylnitrile

[0088] Group Mass loss rate before and after immersion / % Wear amount / mg Example 1 0.382 6.5 Example 10 0.455 7.5 Embodiment 11 0.443 7.3 Comparative Example 12 0.416 7.1 Comparative Example 13 0.395 6.9 Comparative Example 4 0.493 7.8 Comparative Example 5 0.487 7.8

[0089] It can be seen from the data in Table 4 that compared with Examples 1, 10, 11, 12, and 13, the concentration of the sodium hydroxide aqueous solution and the amount of azobisisobutylnitrile added will affect the performance of the stainless steel pipe. Among them, the mass loss rate of the sample in Example 1 before and after immersion is the smallest, and the wear amount is the least, indicating that the corrosion resistance and wear resistance of the stainless steel pipe in Example 1 are the best. Therefore, the sodium hydroxide aqueous solution and the amount of azobisisobutylnitrile added selected in Example 1 are both optimal;

[0090] By comparing Example 1 with Comparative Examples 4 and 5, it can be seen that when the sodium hydroxide aqueous solution is added once or at a constant concentration, the corrosion resistance and wear resistance of the sample will deteriorate. This may be because adding the sodium hydroxide aqueous solution in batches and changing the concentration of the sodium hydroxide aqueous solution can control the hydrolysis rate of methyltrichlorosilane and ensure the modification effect. Therefore, the concentration and addition method of the sodium hydroxide aqueous solution selected in Example 1 are better.

[0091] 5. Explore the effects of coating liquid spraying amount and baking parameters on the performance of stainless steel pipes

[0092] Using Examples 1, 14, 15, 16, and 17 as experimental comparisons, the effects of different spraying amounts of the coating liquid and different baking parameters on the performance of the stainless steel pipe are shown in Table 5 below:

[0093] Table 5 Performance of stainless steel pipes under different spraying amounts of coating liquid and different baking parameters

[0094] Group Mass loss rate before and after immersion / % Wear amount / mg Example 1 0.382 6.5 Embodiment 14 0.397 6.7 Embodiment 15 0.380 6.5 Comparative Example 16 0.413 6.9 Comparative Example 17 0.425 7.1

[0095] It can be seen from the data in Table 5 that: compared with Examples 1, 14, and 15, as the amount of coating liquid spraying increases, the corrosion resistance and wear resistance of the sample are improved, until the corrosion resistance and wear resistance of the sample of Example 1 reach the best. As the amount of coating liquid spraying continues to increase, the corrosion resistance and wear resistance of the sample begin to have no obvious change. Therefore, from a cost perspective, the amount of coating liquid spraying selected in Example 1 is the best.

[0096] Compared with Examples 1, 16 and 17, the mass loss rate of the sample in Example 1 before and after immersion is the smallest and the wear amount is the least, indicating that the corrosion resistance and wear resistance of the stainless steel pipe in Example 1 are the best, so the baking parameters selected in Example 1 are the best.

Claims

1. A composite stainless steel pipe with a corrosion-resistant layer coated on the surface, characterized in that: The invention is composed of a stainless steel pipe and a corrosion-resistant layer coated on the surface of the stainless steel pipe, wherein the components of the stainless steel pipe include, by mass percentage, 14-18% Cr, 6-9% Ni, 0.6-1.2% Mn, 0.02-0.08% C, 0.3-0.6% Si, 1.0-1.6% Cu, and the rest is Fe; The corrosion-resistant layer is formed by curing the coating liquid, and the components of the coating liquid include, by mass percentage: 25-30% of polyacrylate-modified methyl silicone resin, 6-12% of nano-SiC, 4-8% of sodium dodecyl sulfonate, 2-4% of silane coupling agent, and the balance is ethyl acetate.

2. The composite stainless steel pipe with a surface coated with a corrosion-resistant layer according to claim 1, characterized in that: The silane coupling agent is a mixture of any one or more of vinyl trichlorosilane, vinyl trimethoxysilane, vinyl triethoxysilane and 3-aminopropyl triethoxysilane in any ratio.

3. The composite stainless steel pipe with a corrosion-resistant layer coated on the surface according to claim 1, characterized in that: The preparation method of the polyacrylate-modified methyl silicone resin comprises the following steps: S1. Add methyltrichlorosilane and dimethyldichlorosilane into xylene and stir for 3-5 minutes to obtain a mixed solution; wherein the mass ratio of methyltrichlorosilane, dimethyldichlorosilane and xylene is 5-7:1-2:20-25; S2, using sodium hydroxide aqueous solution to adjust the pH value of the mixed solution to 10-11, after reacting for 1-1.5 hours, adding methyl acrylate to obtain a prepolymer, during the reaction, adding sodium hydroxide aqueous solution to the mixed solution once every 20-30 minutes to adjust the pH value of the mixed solution to 9-10; the amount of methyl acrylate added accounts for 15-20% of the mass of the mixed solution; S3, heating the prepolymer to 40-50° C., then adding azobisisobutylnitrile to the prepolymer, continuing to heat the prepolymer to 70-80° C. and keeping the temperature for 10-14 hours under high-speed stirring, and obtaining a polymer after cooling; the amount of azobisisobutylnitrile added accounts for 4-6% of the mass of the prepolymer; S4, distilling the polymer to remove xylene to obtain a solid polymer, and washing and drying the solid polymer to obtain a polyacrylate-modified methyl silicone resin.

4. The composite stainless steel pipe with a surface coated with a corrosion-resistant layer according to claim 3, characterized in that: In step S2, the mass concentration of the sodium hydroxide aqueous solution added initially is 25-30%, and the mass concentration of the sodium hydroxide aqueous solution added subsequently each time is reduced by 2-4% compared with the previous addition.

5. The composite stainless steel pipe with a surface coated with a corrosion-resistant layer according to claim 3, characterized in that: In step S3, the stirring speed under the high-speed stirring state is 600-800 r / min.

6. The composite stainless steel pipe with a surface coated with a corrosion-resistant layer according to claim 3, characterized in that: In step S3, the cooling is performed by using ice water at 0-5°C to cool the prepolymer.

7. The composite stainless steel pipe with a corrosion-resistant layer coated on the surface according to claim 1, characterized in that: The coating liquid is prepared by adding nano-SiC into ethyl acetate, ultrasonically dispersing for 10 to 15 minutes, gradually adding a silane coupling agent during the ultrasonic dispersion process, then adding polyacrylate-modified methyl silicone resin and sodium dodecyl sulfonate into ethyl acetate, stirring until completely dissolved, and obtaining a coating liquid.

8. A method for preparing a composite stainless steel pipe with a surface coated with a corrosion-resistant layer, for preparing the composite stainless steel pipe with a surface coated with a corrosion-resistant layer as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1: grinding, pickling and drying the surface of the stainless steel tube to obtain a pretreated stainless steel tube; Step 2: Spray the coating liquid onto the pretreated stainless steel pipe surface. The spraying amount of the coating liquid is 20-30 ml / cm 2 After the coating liquid completely covers the surface of the stainless steel pipe, the stainless steel pipe is placed at 120-140°C and baked for 2-3 hours. After baking, a composite stainless steel pipe with a surface coated with a corrosion-resistant layer is obtained.

9. The method for preparing a composite stainless steel pipe with a corrosion-resistant layer coated on the surface according to claim 8, characterized in that: The pickling method comprises: soaking the stainless steel pipe in a nitric acid solution with a mass concentration of 10 to 20% for 15 to 20 minutes, and washing the stainless steel pipe with deionized water after the soaking is completed.